A novel low-pressure hybrid dry ice blasting system for improving the tribological and machining characteristics of AISI-52100 tool steel. (August 2022) - Jamil, Muhammad; He, Ning; Zhao, Wei; Khan, Aqib Mashood; Xiang, Huang; Gupta, Munish Kumar; Iqbal, Asif
Abstract: Hybrid minimum quantity lubrication and compressed carbon dioxide (MQL + CO2 ) lubri-coolant can play a crucial role in advancing machinability as well as sustainability. However, it is also the fact that the high-pressure throttling of CO2 produces fog and hinders the low-pressure MQL mist to touch the cutting zone adequately. Therefore, a low-pressure novel hybrid MQL-dry ice blasting lubri-coolant technology is anticipated to improve the machinability by providing the cooling and lubrication simultaneously in milling AISI-52100. This low-pressure hybrid dry ice blasting not only reduces an abundance of smog to reduce the cutting zone visibility, but the dry ice grains also behave as carriers to bring MQL-mist to the cutting zone perfectly. In this proposed study, the surface roughness, residual stresses, cutting temperature, surface hardness, tool wear, and cutting forces are measured by varying the cutting speed (75-300 m/min) and feed per tooth (0.04–0.12 mm/z) under hybrid MQL-dry ice blasting lubri-cooling condition in milling AISI52100 tool steel. The results of this study highlighted that as the cutting speed raised from 100 m/min to 300 m/min, an increase in cutting temperature was 22 % at a constant feed per tooth of 0.08 mm/z. Similarly, the decrease in surface roughness was 42 %, tool life reduced to 57 %, surface hardness increased to 9 %, and across-the-feed surface hardness increased to 58 % by the increase of cutting speed from 75 to 300 m/min and constant feed per tooth of 0.08 mm/z. The proof-of-the-concept study showed the machinability advancement under hybrid lubri-cooling technology due to precise penetration of MQL mist and dry ice grains into the cutting zone in terms of ease in chip evacuation, excellent lubrication, and cutting heat dissipation by sublimation of dry ice.